A continuous kinematic calibration method for accuracy maintenance of industrial robot based on recursive least squares algorithm - Guifang Qiao; Xinyi Jiang; Mingyu Zhang; Chunhui Gao; Ying Zhang (Scientific Reports)
Abstract Industrial robots have become more and more important in the advanced manufacturing industry. There is still a degradation problem in the accuracy performance of industrial robots after being calibrated. To maintain the accuracy performance of robots timely, a continuous kinematic calibration method is proposed. Firstly, the Modified DH (MDH) model and kinematic error model of the industrial robot have been established. Secondly, four groups of poses are measured to demonstrate the degradation of the robot’s accuracy performance. Thirdly, the continuous kinematic calibration method for accuracy maintenance based on the recursive least squares (RLS) algorithm is introduced. Finally, several experiments were conducted to verify the efficiency of the continuous calibration method based on the RLS algorithm. The RLS algorithm can achieve better efficiency and stability than the Levenberg–Marquardt (LM) algorithm. When 15 updated poses are used for parameter identification, the continuous calibration method based on the RLS algorithm can improve accuracy by 84.31%. Besides, the proposed continuous calibration method based on the RLS algorithm not only can save calculation time by 69.52% but also can reduce measurement time by 70%.